2016
DOI: 10.1615/critrevoncog.2017021307
|View full text |Cite
|
Sign up to set email alerts
|

Review of Triple Negative Breast Cancer and the Impact of Inducible Nitric Oxide Synthase on Tumor Biology and Patient Outcomes

Abstract: Triple negative breast cancers (TNBCs), which are defined as estrogen-receptor, progesterone-receptor, and HER2-receptor negative, account for 10-20% of breast cancers, and they are associated with early metastasis, chemotherapeutic resistance, and poor survival rates. One aspect of TNBC that complicates its prognosis and the development of new molecular therapeutic targets is its clinical and molecular heterogeneity. Herein we compare TNBC and basal cytokeratin-positive breast cancers. We examine the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 116 publications
0
30
0
Order By: Relevance
“…TNBC expresses higher levels of nitric oxide (NO), which is estimated by nitrate levels, than HER2+ or luminal breast cancers [ 47 ]. Furthermore, previous in vitro studies have shown that TNBC tumors expressing inducible nitric oxide synthase (iNOS) produce moderate to high levels of NO, and the increased iNOS activity may confer resistance to chemotherapy [ 48 ]. A preclinical study demonstrated that combining docetaxel with pan-NOS inhibitor NG-monomethyl- l -arginine acetate (L-NMMA) in a xenograft model of MDA-MB-231 decreased Ki67 proliferating cells, enhanced tumor apoptosis, and reduced tumor-initiating capacity of residual tumor cells after chemotherapy to a larger degree than docetaxel alone [ 29 ].…”
Section: Molecular Alterations In Mpbcmentioning
confidence: 99%
“…TNBC expresses higher levels of nitric oxide (NO), which is estimated by nitrate levels, than HER2+ or luminal breast cancers [ 47 ]. Furthermore, previous in vitro studies have shown that TNBC tumors expressing inducible nitric oxide synthase (iNOS) produce moderate to high levels of NO, and the increased iNOS activity may confer resistance to chemotherapy [ 48 ]. A preclinical study demonstrated that combining docetaxel with pan-NOS inhibitor NG-monomethyl- l -arginine acetate (L-NMMA) in a xenograft model of MDA-MB-231 decreased Ki67 proliferating cells, enhanced tumor apoptosis, and reduced tumor-initiating capacity of residual tumor cells after chemotherapy to a larger degree than docetaxel alone [ 29 ].…”
Section: Molecular Alterations In Mpbcmentioning
confidence: 99%
“…We assessed whether IS can modulate cancer hallmarks that were modulated by other cytostatic bacterial metabolites [ 16 , 17 , 41 , 47 , 61 , 62 , 63 , 64 , 65 ]. First, we assessed oxidative/nitrosative stress markers, as these are major regulators of cancer hallmarks and cancer progression [ 66 , 67 , 68 , 69 , 70 ]. Levels of thiobarbituric acid-reactive substances (TBARS) and 4-hydroxynonenal (4HNE), both markers of lipid oxidative damage, increased when cells were treated with IS ( Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Principal et al [28] suggested that higher levels of iNOS may serve as a marker of poor prognosis and aggressiveness in patients with breast cancer. Wash et al [29] showed that iNOS has been shown to induce p53 mutation accumulation and activation of the epidermal growth factor receptor; all of which are key components of breast cancer biology. Moreover, iNOS predicts poor outcome in breast cancer, and iNOS inhibitors show efficacy when used in combination with chemotherapy.…”
Section: Immunohistochemical Resultsmentioning
confidence: 99%